The hidden army: how a GP-patient volunteer group responded to covid-19. (15th December 2020) - Jenner, Chris; Szasz, Carly; Martin, Jacqui; Herman, Laura; Bekhor, Josh
Abstract : When the UK government declared a national lockdown on 23 March 2020, staff at Elliott Hall Medical Centre in Harrow recognised that many of their vulnerable patients would find it difficult to cope. To help them, the practice called on volunteers within its patient community to assist. Here they describe what they did and how they continue to work with patient volunteers in the next phase of the pandemic.